Metagenomic prospection of quorum sensing related bacteria during spontaneous cocoa beans fermentation - Almeida, Otávio Guilherme Gonçalves de (2022)
In order to obtain processed chocolate with high standards it is mandatory the fermentation of cocoa seeds, which are the raw material for chocolate production. After cutting of cocoa fruits, the autochthonous microbiota infiltrates, and enters in contact with the seeds, contaminating them. As the seeds are surrounded by a mucilaginous pulp, which is rich in nutrients and presents high water activity, microorganisms find adequate conditions to proliferate and growth. Among the possible microorganisms related to cocoa fermentation, yeast, lactic acid bacteria (LAB), and acetic acid bacteria (AAB) stand out, as these groups are related to a well-defined microbial succession along cocoa fermentation. This process allows the pulp drainage and stimulates the endogenous hydrolases to metabolize the stored substrates in the seeds. The microbial activity in consonance with the intrinsic metabolic activity of the seeds leads to the releasing of chocolate\'s flavour precursors. Many authors attribute to cross feeding the main role guiding and shaping microbial succession, since the yeasts depectinize the pulp releasing sugars that can be metabolized by LAB. The LAB convert these sugars into lactic acid, mannitol, and acetic acid. Mannitol is metabolized by AAB as carbon source, resulting in more acetic acid released by bacterial metabolism. Although the cross feeding explains microbial succession in cocoa fermentation, under the point of view of microbial ecology, literature on the microbial interactions in cocoa fermentation is scarce, specifically the occurrence and influence of quorum sensing (QS), for instance. It is known QS is a process of synchronization of gene expression intermediated by autoinducer molecules (AIs) in high cell densities conditions. As cocoa fermentation presents all the conditions for microbial enrichment and some studies have shown that bacteria related to QS may present competitive advantages in harsh environments, this research aimed initially to identify, by metagenomics, the QS related microbiota through the monitoring of the gene luxS along fermentation. Besides, bacterial genomes recovered from spontaneous fermentation were also investigated for the presence of this gene. The luxS gene is recognized as a universal QS marker because it characterizes the interspecific cell to cell communication. In the first Chapter of this work, it is presented a metagenomic analysis of an entire spontaneous cocoa fermentation sampled during 144h of fermentation. The data revealed the fungi were present along the entire fermentative process. Moreover, it was also demonstrated that reads related to the luxS gene are enriched as fermentation progresses, reaching a maximum at 72h of fermentation. It was also observed the genera Enterobacter, \"Lactobacillus\", Bacillus, and Pantoea were associated with luxS gene, which allowed to track the operational taxonomic units related to QS in cocoa fermentation. In the second Chapter, a comparative genomic analysis is presented. In that study, three strains of the species Lactiplantibacillus plantarum Lb2, Limosilactobacillus fermentum Lb1, and Pediococcus acidilactici P1 isolated from a spontaneous cocoa fermentation had their genomes sequenced and compared against all publicly available genomes of cognate species. The results shown the gene luxS is detected in all strains of this species and Lp. plantarum species in particular presents six luxS gene clusters, highlighting the high copy number of this gene in Lp. plantarum strains. For Lm. fermentum, there were only two gene clusters, and in P. acidilactici a single gene cluster. Phylogenetic analysis has shown the second gene cluster (named luxS_2) of Lm. fermentum was horizontally transferred by transduction from a Lp. plantarum strain to a Lm. fermentum strain, as both species present the same gene cluster and the flanking region of this cluster in Lm. fermentum was composed by IS30 transposases. In addition, luxS homologous sequences were determined by multiple alignment analysis to draw species- and clade-specific primers for rapid screening of strains to evaluate their potential related to QS and for qRT-PCR purposes. In the third Chapter, it is presented a comparative genomic analysis for AAB isolated from a spontaneous cocoa fermentation process, whose strains MRS7, GYC10, GYC12, GYC19, and GYC27 belonged to A. senegalensis species and were genotypically diverse, had their genomes sequenced and compared with public databases available for A. senegalensis strains at the time of publication. The study has shown A. senegalensis did not carry any luxS gene, but it presented genes related to intraspecific QS, such as acylhomoserine lactones (AHLs) and response regulators, as well as genes related to QS inhibition such as acylases and lactonases, corroborating the previous analyses presented in the first Chapter of this thesis. Besides, as AAB present potential to be applied in several industrial processes, such as cellulose production and vinegar fermentation, the metabolic pathways involved with bacterial adaptation to stressing conditions were investigated. The results shown these strains presented a good genetic repertoire related to bacterial adaptation to harsh environments, indicated by the presence of chaperones, alcohol dehydrogenases, and ABC proteins that confer tolerance to high concentrations of ethanol and high temperature. Additionally, the strains did not present pathogenic potential, as indicated by the absence of antibiotic resistance genes. In this way, the results suggested these strains of A. senegalensis isolated from cocoa fermentation could be applied also in other industrial processes. Finally, in the fourth Chapter the outcome of the Ph.D project is presented in a submitted manuscript showing the in situ detection of the luxS gene in lab scale fermentation. Thus, seven distinct fermentations were performed. The control fermentation (named F0) was conducted without duplicate, while the remaining fermentations, named F1, F2, and F3 were performed in duplicates, and inoculated with distinct combinations of cocktails containing yeasts, LAB, and/or AAB. The objective of that work was to compare the luxS gene expression along 96h of fermentation in each replicate and in the control (non inoculated fermentation - F0). In parallel, analyses for selective microbial enumeration, pH, and temperature monitoring, as well as metagenomics (16S rRNA and ITS), enzymatic activity dosage, and gas-chromatography coupled with mass spectrometry (GC-MS) for detection of volatile organic metabolites (VOCs) were performed to correlate QS potential with cocoa fermentation quality. The results revealed that even in laboratory conditions the microbial succession was observed for all fermentations, which was corroborated by microbial enumeration and metataxonomic analysis. However, no statistical difference was observed for presumptive microbial enumeration of the F0 and experimental fermentations (p > 0.05), which was also reinforced by the absence of significative difference for α-diversity metrics determined by metataxonomics among the fermentations. Additionally, no statistically significant differences of enzymatic activities were detected, and there were no microbial amplicon sequence variants correlated with enzymatic activities, suggesting the enzymatic activity was mainly shaped by endogenous hydrolases of the seeds and not by the microbial shifts per se. Regarding the luxS gene measurements for Lp. plantarum and Lm. fermentum species, it was observed the luxS genes of Lp. plantarum were active during all fermentation period, while Lm. fermentum luxS genes were detected during the first 72h of fermentation. The correlation between quality of fermentation and luxS gene expression evidenced a positive association of Lp. plantarum with undesirable sensorial attributes for fermented seeds. Based on the results of this work, it is possible to affirm that the luxS gene is active during cocoa fermentation, as presented in the first Chapter and there was progress in the understanding of the dynamics of cocoa fermentation, with demonstration of different enzymes acting along fermentation. In addition, the results of this research consolidate the hypothesis that Lp. plantarum is a possible protagonist in this type of fermentation, with great potential for expressing QS pathways. Future studies may apply the data collected throughout this study under field conditions.